Jaký prostor věnují média prevenci a časné detekci chronického onemocnění ledvin - Tong, A; Chapman, S; Sainsbury, P; Craig, J. C (Postgraduální nefrologie, 2008)
News media raise public awareness about health and can influence public policy agenda. Recently, nephrologists have sought to make prevention and early detection of chronic kidney disease (CKD) a health care priority. We assessed the extent and manner in which Australian television news and newspapers cover CKD prevention or early detection. Electronic news databases for print media and television programs were searched (May 2005 to March 2007) for items referring to CKD prevention or early detection. We analyzed all relevant items for spokespeople, main news frame, focus of responsibility, proposed solutions, and trigger/reason for publication. Of 2,439 newspaper articles and 10,430 television broadcasts retrieved, only 214 articles (8.77%) and 7 broadcasts (0.06%) were eligible. Kidney transplantation dominated CKD-related news. Lay person or high-profile advocates were virtually absent. Risks of cardiovascular disease and mortality conferred by CKD were not emphasized by news reports; instead, CKD received peripheral mention as a secondary consequence of diabetes or obesity. Few reports cited the economic consequences of CKD. The media focused on lifestyle causes and solutions, whereas nonlifestyle causes and screening and prevention strategies were rarely mentioned. Kidney health professionals need to actively engage with the media in efforts to amplify desired messages on CKD prevention or early detection. Medical journals, research institutions, universities, hospitals, and advocacy groups should issue press releases that highlight newsworthy aspects of this topic. Extending news media coverage can help exert an influence on health policies and agenda setting and increase public awareness to improve prevention and early detection of CKD.
Keywords: Health Education; primární prevence; Australia; Primary Prevention; Renal Insufficiency, Chronic; lidé; Sensitivity and Specificity; senzitivita a specificita; chronická renální insuficience; Austrálie; časná diagnóza; Risk Factors; Evaluation Studies as Topic; hodnotící studie jako téma; zdravotní výchova; rizikové faktory; Early Diagnosis; Mass Media; hromadné sdělovací prostředky; Humans